2006
DOI: 10.1111/j.1744-7976.2006.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes and Acceptance of CLA‐Enriched Dairy Products

Abstract: "Consumers have increasingly recognized the link between health and diet, and are taking special interest in functional foods that promise to enhance health and reduce the risk of diseases. Milk, an excellent source of essential nutrients, as well as an ideal carrier of healthy functional ingredients, holds promise for the development of functional foods. A variety of functional milk products have been launched into the market, such as yogurt, milk, butter and cheese fortified with vitamins, minerals, and omeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 17 publications
4
53
0
3
Order By: Relevance
“…Therefore it would seem logical that the biggest market potential for nutritional and health claims related to fat content is to be developed in products perceived to have high fat content, if producers want to remain in the market. Peng et al (2006) already state that health claims, specially if not counter-intuitive, can increase interest in products perceived as less healthy, a conclusion in line with BechLarsen et al (2001) who conclude that enrichment (in our case fat reduction) is found more justified in this type of products. Developments in the sausage market towards the use of other meats with less fat (i.e.…”
Section: Product Selectionsupporting
confidence: 74%
“…Therefore it would seem logical that the biggest market potential for nutritional and health claims related to fat content is to be developed in products perceived to have high fat content, if producers want to remain in the market. Peng et al (2006) already state that health claims, specially if not counter-intuitive, can increase interest in products perceived as less healthy, a conclusion in line with BechLarsen et al (2001) who conclude that enrichment (in our case fat reduction) is found more justified in this type of products. Developments in the sausage market towards the use of other meats with less fat (i.e.…”
Section: Product Selectionsupporting
confidence: 74%
“…Education level and age of specialty milk consumers are also slightly higher compared to others. According to Peng, West, and Wang (2006) if consumers are well-informed about the health benefits of functional enhancements, their attitude toward functional enhancements will greatly improve. Lohr (2001) also suggests that income, lifestyle decisions and food safety concerns affect consumers' decision to purchase functionally enhanced dairy products.…”
Section: First Stage Modelmentioning
confidence: 98%
“…The explanatory variables are based on the implicit attribute prices from the first stage and the household demographics. Peng et al (2006) indicate that health concerned consumers are willing to pay a higher premium for functional enhancements in dairy products. Our results are consistent with their findings: smaller and elderly households have more health related concerns and they have a higher probability of participating in the specialty milk market.…”
Section: Discussionmentioning
confidence: 99%